1993
DOI: 10.1056/nejm199311253292201
|View full text |Cite
|
Sign up to set email alerts
|

The Limit of Viability -- Neonatal Outcome of Infants Born at 22 to 25 Weeks' Gestation

Abstract: We believe that aggressive resuscitation of infants born at 25 weeks' gestation is indicated, but not of those born at 22 weeks. Whether the occasional child who is born at 23 or 24 weeks' gestation and does well justifies the considerable mortality and morbidity of the majority is a question that should be discussed by parents, health care providers, and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
160
2
10

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 419 publications
(182 citation statements)
references
References 21 publications
10
160
2
10
Order By: Relevance
“…At the same time, the GA at which 50% or more infants survived decreased from 28 to 23 weeks. Similar results have been reported by Allen et al 21 in 1993 and Hack et al 23 in 1995 with 56% and 54% survival at 24 weeks GA. Survival for the infants presented by O'Shea et al 24 in 1997 increased from 31% at 23 weeks to 63% at 24 weeks.…”
supporting
confidence: 89%
“…At the same time, the GA at which 50% or more infants survived decreased from 28 to 23 weeks. Similar results have been reported by Allen et al 21 in 1993 and Hack et al 23 in 1995 with 56% and 54% survival at 24 weeks GA. Survival for the infants presented by O'Shea et al 24 in 1997 increased from 31% at 23 weeks to 63% at 24 weeks.…”
supporting
confidence: 89%
“…[8][9][10][11][12] In an earlier study, although approximately 10% of neonates born at 22 weeks' gestation survived to admission to the NICU, none of them were alive by 6 months of age. 18 In more recent studies, none of the infants born at <23 weeks were reported to survive to discharge from the NICU. [19][20] It appears that these findings, and perhaps the practicing neonatologists' own experiences, have influenced the approach to the management provided in the delivery room to the smallest and most immature neonates, as a recent survey of academic and private neonatologists in the United States has found that only 4% of the participants would resuscitate a neonate at 23 weeks' gestation with a birth weight of <500 g. 12 It further states that 57% of the responders would provide comfort care only, and 36% would defer the decision to parental wishes for these extremely immature infants.…”
Section: Resultsmentioning
confidence: 97%
“…2 In addition, most previous reports were not population based, as they examined pooled data over several years of a small number of infants who were treated in different ways. [3][4][5][6][7] The aim of the present study was to examine GAspecific outcomes of a large population-based cohort of infants who were born at Յ26 weeks' gestation and cared for in all 19 perinatal centers of Belgium between January 1999 and December 2000 and to compare the results with those of other geographic GA-based cohorts available in the literature. [8][9][10][11][12][13][14][15] …”
mentioning
confidence: 99%